Effects of High-Dose Rosuvastatin on Ventricular Remodelling and Cardiac Function in ST-Segment Elevation Myocardial Infarction - Luo R; Sun X; Shen F; Hong B; Wang Z (Dove Medical Press, 2020)
Rong Luo ,* Xiaochen Sun ,* Feiyan Shen, Bin Hong, Zilong Wang Department of Cardiology, Qingpu Medical Center, Zhongshan Hospital, Fudan University, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zilong Wang Email wangthinker123@outlook.comObjective: To investigate the effects of high-dose rosuvastatin on ventricular remodelling and cardiac function in ST-segment elevation myocardial infarction (STEMI).Materials and Methods: From January 2017 to March 2019, the clinical data of 93 patients with STEMI were collected and analysed, with 46 cases in the conventional-dose group (rosuvastatin, 10 mg/d) and 47 cases in the high-dose group (rosuvastatin, 20 mg/d). Blood lipid (TC, TG, LDL-C and HDL-C), serum inflammatory markers (hs-CRP, IL-6, TNF-α and ICAM-1), ventricular remodelling markers (NT-pro BNP, MMP-9, TIMP-4 and Gal-3) and indicators of cardiac function (LVESD, LVESD, LVESV, LVEDV, IVST and LVEF) were collected from all patients at the time of admission and 8 weeks after rosuvastatin treatment.Results: After treatment with rosuvastatin for 8 weeks, compared with those in conventional-dose group, the levels of TC, TG, LDL-C, hs-CRP, IL-6, TNF-α, ICAM-1, NT-pro BNP, MMP-9 and Gal-3 in the high-dose group decreased significantly (P< 0.05), while the increase of HDL-C and TIMP-4 levels was more obvious (P< 0.05) than that in the conventional-dose group. Moreover, LVEF was significantly higher (P< 0.05) and LVESD, LVESD, LVESV, LVEDV and IVST were significantly lower (P< 0.05) after treatment than before treatment in both groups. The improvement of cardiac ultrasound results in the high-dose group was more significant than that in the conventional-dose group (P< 0.05).Conclusion: This study suggests that high-dose rosuvastatin was better than conventional-dose rosuvastatin for improving blood lipid metabolism, reducing the inflammatory response, and preventing and treating ventricular remodelling and myocardial fibrosis, indicating that high-dose rosuvastatin had stronger therapeutic effect on STEMI than conventional-dose rosuvastatin.Keywords: rosuvastatin, ST elevation myocardial infarction, blood lipids, inflammatory factor, ventricular remodelling, myocardial fibrosis